ESL learners' use of metacognitive reading strategies: an exploratory study / Fatin Thuraiya Abd. Karim - Abd. Karim, Fatin Thuraiya (Faculty of Education, 2010)
This study investigated the ESL learners metacognitve awareness and reading strategies use of 80 Form Four of a secondary school in relation to language proficiency. Specifically, it examined the types and frequency of reading strategies used by the high and low language proficiency students and the differences between them. Additionally, the study attempted to fmd out the relationship between the ESL learners' overall language proficiency performance and their frequency of use of reading strategies of the overall and three sub-categories of reading strategies namely, global, problem- solving and support strategies. The research design is a cross sectional survey research which used the Survey of Reading Strategies (SORS) questionnaire developed by Mokhtari and Sheorey (2002). The independent variable was the language proficiency of the ESL learners and the dependent variable was the metacognitive awareness of ESL learners, measured in terms of their ratings of the three sub-categories of reading strategies. Data obtained from the questionnaire were analyzed using One-way ANOVA, independent sample t-test and Pearson's Product Moment Correlation Coefficient. The findings of this study revealed that the high and low language proficiency students were active reading strategy users. High language proficiency students used problem solving strategies with higher frequency than global and support strategies while low language proficiency students used problem -solving and support strategies with higher frequency than the global strategies. Next, the results seemed to suggest that high and low language proficiency students used somewhat similar frequency of overall, global, problem-solving and support strategies. Moreover, there was no significant relationship between the ESL learners' overall language proficiency performance and their frequency of use of overall, global, problem-solving and support strategies. This study also provides pedagogical implications and suggests area for future research.